A twenty-year partnership of practice and research: The Nobel laureates and Pratham in India. (March 2020) - Banerji, Rukmini; Chavan, Madhav
Abstract: Pioneered by Pratham, "teaching at the right level" (TaRL) is a well-known and effective approach for improving basic reading and arithmetic capabilities of primary school children. This method is particularly appropriate for children who have been in school for a few years but for various reasons have not acquired foundational skills. The evolution of this approach has occurred over a period of almost two decades. The story of how this approach was developed provides a fascinating case of how innovative interventions and rigorous evidence can go hand in hand. Today TaRL is one of the most effective ways to improve children's learning. It has been used widely in India and now increasingly is being tried in sub Saharan Africa. This contribution outlines main milestones of this joint journey and discusses what made this evolution effective.